2009
DOI: 10.1093/jnci/djp123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cancer on Health-Related Quality of Life of Older Americans

Abstract: These findings provide validation of the specific deleterious effects of cancer on HRQOL and an evidence base for future research and clinical interventions aimed at understanding and remediating these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
184
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(199 citation statements)
references
References 27 publications
8
184
3
4
Order By: Relevance
“…Although those with a lung cancer diagnosis were the largest group, they were the least likely to be seen by an occupational therapist. This finding is disconcerting because the literature shows that older adults with lung cancer are most likely to experience a decline in ADLs, specifically, bathing, dressing, getting in and out of a chair, and using the toilet, after their diagnosis (Reeve et al, 2009). Compared with breast cancer, adults with lung cancer were more likely to report poorer health status (Hewitt, Rowland, & Yancik, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although those with a lung cancer diagnosis were the largest group, they were the least likely to be seen by an occupational therapist. This finding is disconcerting because the literature shows that older adults with lung cancer are most likely to experience a decline in ADLs, specifically, bathing, dressing, getting in and out of a chair, and using the toilet, after their diagnosis (Reeve et al, 2009). Compared with breast cancer, adults with lung cancer were more likely to report poorer health status (Hewitt, Rowland, & Yancik, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Within oncology research, Sehl, Satariano, Ragland, Reuben, and Naeim (2009) found that limitations in ADLs and IADLs persisted beyond 1 yr for older women with breast cancer. In addition, Reeve et al (2009) examined adults with cancer pre-and postdiagnosis and found that although some older adults were able to improve within the first year, others did not recover compared with the general health scores of adult control participants without cancer more than 19 mo after the cancer sample's diagnoses. Thus, the 2-yr time period was chosen based on clinical experience of the first author (Pergolotti) and the literature describing functional deficits from a cancer diagnosis as still present after 1 yr or longer (Deimling, Sterns, Bowman, & Kahana, 2005;Reeve et al, 2009;Sehl et al, 2009;Sehl, Lu, Silliman, & Ganz, 2013).…”
Section: Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Service planners and providers need to consider the health and social care requirements for cancer survivorship as cancer patients and their caregivers experience poorer health than the general population several years after treatment has ended (Santin et al, 2012, Santin et al, 2013, Elliott et al, 2011, Hewitt et al, 2003, Schultz et al, 2003, Yabroff et al, 2004, Deimling et al, 2005, Keating et al, 2005, Nord et al, 2005, Eakin et al, 2007and Reeve et al, 2009. There is common agreement that there is a need to reconfigure current follow-up services for cancer patients in order to improve the match between care needs and service responses and to improve the efficiency and effectiveness of the cancer care system.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited empirical evidence regarding the long term health and wellbeing of cancer survivors, and even less information regarding health care needs and health service utilisation. The few international studies available [3][4][5][6][7][8][9][10] suggest that cancer survivors experience poorer health and wellbeing and have a higher level of health service utilization compared to the general population. These studies however are limited methodologically and there are no studies that have been undertaken in Northern Ireland or in the Republic of Ireland.…”
Section: Introductionmentioning
confidence: 99%